Gandhian way : peace, non-violence, and empowerment - International Conference on Peace, Non-violence, and Empowerment: Gandhian Philosophy in the 21st Century (2007 January 29-30 : New Delhi, India); Sharma, Anand, 1953- (Darya Ganj, New Delhi, India : Academic Foundation, 2007)
Ponencias presentadas durante la Conferencia Internacional sobre la Paz, la No Violencia y Empoderamiento: Filosofía de Gandhi en el siglo 21, convocada por el Congreso Nacional de la India en Nueva Delhi los días 29 a 30 en 2007.
"Indian National Congress."
"Celebrating Hundred Years of 'Satyagraha' (1906-2006)"--P. facing t.p.
Keywords: GANDHI, MOHANDAS KARAMCHAND, -- 1869-1948 -- PENSAMIENTO FILOSOFICO; EMPODERAMIENTO -- CONGRESO, CONFERENCIA, ETC; PACIFISMO -- CONGRESO, CONFERENCIA, ETC